Teaching Facilitation of Family Participation in Educational Institutions - Gomariz, María Ángeles; Parra, Joaquín; García-Sanz, María Paz; Hernández-Prados, María Ángeles (Frontiers in Psychology, 2022)
The participation of families in schools where their children study is a recurring research topic. This field tends to address the perception of parents or teaching staff. This article is novel in that it considers what teachers, and not families, do to facilitate this participation. The purpose of the study has been to contrast a theoretical model with a multidimensional questionnaire designed to obtain information on the assistance provided by teachers to improve parental involvement in schools. It will allow us to lay the foundations for the content necessary for the initial and permanent training of teachers. Then, an initial questionnaire was created and, after being subjected to expert judgment, it was applied to 225 Spanish teachers, using a quantitative, non-experimental methodology. After calculating the exploratory and confirmatory factor analysis and applying the structural equation model, a questionnaire (QFIS-TP) was obtained that had satisfactory construct validity and reliability.